The impact of a child-rights approach to litigation on the realisation of the right to education of pregnant learners in Africa - Akonumbo, Atangcho (University of Pretoria, 2021)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.